Antidiabetic pharmacotherapy and anamnestic hypoglycemia in a large cohort of type 2 diabetic patients$tan analysis of the DiaRegis registry - Tschöpe, Diethelm; Bramlage, Peter; Binz, Christiane; Krekler, Michael; Plate, Tanja; Deeg, Evelin; Gitt, Anselm Kai (Cardiovascular diabetology, 2011)
We aimed to identify predictors of anamnestic hypoglycaemia in type-2 diabetic patients on oral mono- or dual oral combination antidiabetic pharmacotherapy.
Gesehen am 17.11.2022